2021
DOI: 10.1021/acs.jpcb.1c03896
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of Binding Interactions between the Ryanodine Receptor Type 2 and Calmodulin

Abstract: Mutations in the cardiac ryanodine receptor type 2 (RyR2) have been linked to a variety of cardiac arrhythmias, such as catecholaminergic polymorphic ventricular tachycardia (CPVT). RyR2 is regulated by calmodulin (CaM), and mutations that disrupt their interaction can cause aberrant calcium release, leading to an arrhythmia. It was recently shown that increasing the RyR2–CaM binding affinity could rescue a defective CPVT-related RyR2 channel to near wild-type behavior. However, the interactions that determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…Deletion of the sequence 3583-3603aa in RyR2 resulted in disruption of CaM binding to RyR2 and reduced efficacy of CaM inhibition on RyR2 activity in single channel measurements [23]. Besides the 3583-3603aa region, other RyR2 regions have also been reported as potential CaMbinding sequences; however their exact contribution to CaM-binding remains to be fully elucidated [25,29]. Huang et al [30], based on previous binding studies with radio-labeled CaM where sequence 4303-4328 in RyR1 (4261-4286 in RyR2) was first detected as a CaM-binding sequence [4,31], investigated the 3581-3612aa and 4261-4286aa regions of mouse RyR2 as putative CaMBDs by cryo-EM and FRET experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Deletion of the sequence 3583-3603aa in RyR2 resulted in disruption of CaM binding to RyR2 and reduced efficacy of CaM inhibition on RyR2 activity in single channel measurements [23]. Besides the 3583-3603aa region, other RyR2 regions have also been reported as potential CaMbinding sequences; however their exact contribution to CaM-binding remains to be fully elucidated [25,29]. Huang et al [30], based on previous binding studies with radio-labeled CaM where sequence 4303-4328 in RyR1 (4261-4286 in RyR2) was first detected as a CaM-binding sequence [4,31], investigated the 3581-3612aa and 4261-4286aa regions of mouse RyR2 as putative CaMBDs by cryo-EM and FRET experiments.…”
Section: Resultsmentioning
confidence: 99%
“…For this, we switched to a different method that we had used previously to study residue−residue binding interactions in the RyR2-CaM system. 62 S4S5L Interacts with the S6 Helix and the U-Motif. To provide a more detailed analysis of the interactions of the S4S5L with its surrounding environment, we located the primary residue−residue interactions involved in the binding of the S4S5L on a given subunit to its surrounding protein environment within the RyR2.…”
Section: ■ Resultsmentioning
confidence: 99%
“…This similarity suggested that a more detailed analysis at the level of individual residue–residue binding interactions was required. For this, we switched to a different method that we had used previously to study residue–residue binding interactions in the RyR2-CaM system …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CaM has been a subject of interest from the computational community because of its coupling of structures and functions: folding, conformational changes, and Ca 2+ -binding. A few molecular dynamics simulations focus on separate incidences because each of these topics requires enormous computational resources and modeling efforts: CaM’s allostery, , the CaM-target binding, ,, or the coordination chemistry of Ca 2+ in the Ca 2+ -binding loops in CaM. , The energy landscape view for the interplay among folding, allostery, and binding of CaM domains was provided to investigate possible routes CaM might explore in response to external stimuli.…”
Section: Discussionmentioning
confidence: 99%